EFFECT OF STARVATION AND REPEEDING ON TISSUE PROXIMATE ANALYSIS OF HEPATIC AND MUSCULAR TISSUES OF TIL API A MOSSAMBICA (PETERS) - Moorthy, C V Narasimha; Murthy, V Krishna; Reddy, G Vemananda; Haranath, V Bhaskara; Reddanna, P; Govindappa, S (Indian Journal of Fisheries, 2011)
starvation in Tilapia mossambica (Peters) induced higher depletion of carbohydrate reserves in all the tissues. While liver and red muscle showed higher lipoiysis, the white mwscte had higher proteolysis. The refeeding process resulted in replenishment of tissue reservs in white muscle, while those of liver and red muscle were at lower level than normal, suggesting the possibility of impairment of synthetic activities in liver and red muscle after prolonged stairvation. The carbohydrate synthetic efficiency in white muscle seem to be considerably elevated on refeeding. The lipid reserves of all the tissues were depleted even after refeeding and he’nce the course of stairvation and refeeding was envisaged to decrease the tissue fat depots